Computed tomographic features of confirmed gallbladder pathology in 34 dogs. Issue 6 (12th September 2020) - Brand, Emily M.; Lim, Chee Kin; Heng, Hock Gan; Grosso, Federico Vilaplana; Hanlon, Jessica; Jones‐Hall, Yava
Abstract: Gallbladder pathology is common in dogs, but published studies describing the computed tomographic (CT) appearance of many gallbladder pathologies are currently lacking. This retrospective, multicenter, cases series, descriptive study evaluated the CT features of confirmed gallbladder pathology in 34 dogs. In this subset of dogs, the most common pathologies included cystic mucosal hyperplasia (15/34, 44.1%), gallbladder wall edema (9/34, 26.5%), gallbladder mucocele (8/34, 23.5%), bactibilia (7/34, 20.6%), cholecystitis (6/34, 17.6%), white bile (6/34, 17.6%), and cholelithiasis (4/34, 11.8%). The presence of intraluminal nodules, gallbladder wall thickening, hyperattenuating material (35‐100 HU), and mineral attenuating material (>100 HU) were the most common abnormalities detected. However, overlap of each of these findings with a variety of gallbladder pathologies showed that none of the findings were pathognomonic for any of these pathologies. The presence of any of these CT abnormalities should increase the suspicion of gallbladder pathology and prompt further evaluation of the gallbladder for definitive diagnosis.